TikTok sebagai Media Pemasaran Digital di Indonesia - Krisdanu, Cheryl Arshiefa; Kiranastari Asoka Sumantri (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Currently, the presence of technology and the internet has had a significant impact on the marketing field. TikTok social media is a new digital marketing medium that is developing in Indonesia. TikTok users in Indonesia are in second place in the world. This research aims to more specifically explain the use of TikTok as a new marketing medium in Indonesia. By using a systematic literature review with the PRISMA method, several previously relevant scientific journals were found to be used as secondary research sources to answer questions about the use of TikTok as a new marketing medium in Indonesia. The research results show that Tiktok as a digital marketing medium in Indonesia has been used in accordance with the advantages of digital media to create connection or involvement. The use of TikTok has a positive effect on engagement between brands and their audiences and can have a positive impact on purchasing decisions, brand image, brand value, and brand loyalty. To create connections, messages, features, and types of content must be combined appropriately according to the characteristics of the target audience.